Umbilical cord mesenchymal stromal cell-derived extracellular vesicles lack the potency to immunomodulate human monocyte-derived macrophages in vitro - Borges da Silva, Tamiris; Rendra, Erika; David, Christopher A. W.; Bieback, Karen; Cross, Michael J.; Wilm, Bettina; Liptrott, Neill J.; Murray, Patricia (Biomedicine & pharmacotherapy, 2023)
Mesenchymal stromal cells (MSCs) have been reported to display efficacy in a variety of preclinical models, but without long-term engraftment, suggesting a role for secreted factors, such as MSC-derived extracellular vesicles (EVs). MSCs are known to elicit immunomodulatory effects, an important aspect of which is their ability to affect macrophage phenotype. However, it is not clear if these effects are mediated by MSC-derived EVs, or other factors secreted by the MSCs. Here, we use flow cytometry to assess the effects of human umbilical cord (hUC) MSC-derived EVs on the expression of pro-inflammatory (CD80) and anti-inflammatory (CD163) surface markers in human monocyte-derived macrophages (hMDMs). hUC-MSC-derived EVs did not change the surface marker expression of the hMDMs. In contrast, when hMDMs were co-incubated with hUC-MSCs in indirect co-cultures, changes were observed in the expression of CD14, CD80 and CD163, particularly in M1 macrophages, suggesting that soluble factors are necessary to elicit a shift in phenotype. However, even though EVs did not alter the surface marker expression of macrophages, they promoted angiogenesis and phagocytic capacity increased proportionally to increases in EV concentration. Taken together, these results suggest that hUC-MSC-derived EVs are not sufficient to alter macrophage phenotype and that additional MSC-derived factors are needed.
Gesehen am 17.01.2024